Enhancing end of life care on general internal medical wards: the 3 Wishes Project - Julie C. Reid; Brittany Dennis; Neala Hoad; France Clarke; Rajendar Hanmiah; Daniel Brandt Vegas; Anne Boyle; Feli Toledo; Jill C. Rudkowski; Mark Soth; Diane Heels-Ansdell; Andrew Cheung; et al. (BMC Palliative Care, 2023)
Abstract Background Initially developed in the intensive care unit (ICU) at St. Joseph’s Healthcare Hamilton (SJHH) the 3 Wishes Project (3WP) provides personalized, compassionate care to dying patients and their families. The objective of this study was to develop and evaluate 3WP expansion strategies for patients cared for on General Internal Medicine (GIM) wards in our hospital. Methods From January 2020-November 2021, we developed a phased, multicomponent approach for program expansion. We enrolled patients on the GIM wards who had a high probability of dying in hospital, then elicited, implemented, and documented wishes for them or their families. Data were analyzed descriptively. Results From March 2020 to November 2020, we implemented staff education and engagement activities, created an Expansion Coordinator position, held strategic consultations, and offered enabling resources. From March 2020 to November 2021, we enrolled 62 patients and elicited 281 wishes (median [1st, 3rd quartiles] 4 [4, 5] wishes/patient). The most common wish categories were personalizing the environment (67 wishes, 24%), rituals and spiritual support (42 wishes, 15%), and facilitating connections (39 wishes, 14%). The median [1st, 3rd] cost/patient was $0 [0, $10.00] (range $0 to $86); 91% of wishes incurred no cost to the program. Conclusions The formal expansion of the 3WP on GIM wards has been successful despite COVID-19 pandemic disruptions. While there is still work ahead, these data suggest that implementing the 3WP on the GIM wards is feasible and affordable. Increased engagement of the clinical team during the pandemic suggests that it is positively received.